PENGARUH STRATEGI PEMASARAN TERHADAP KEPUTUSAN PEMBELIAN ULANG PADA PRODUK SHARE TEA DI MANADO TOWN SQUARE 3 KOTA MANADO - Dhea Octaviani Sumaila; Joachim N. K. Dumais; Ellen G. Tangkere (Sam Ratulangi University, 2018)
This study aims to determine the effect of marketing strategy on purchasing decisions on Share Tea products in Mantos 3 City Manado. This research is carried out for 3 months from February 2018 until April 2018. Data is done by using primary data and secondary data. Primary data was obtained by interview based on list of questionneire. Sampling method is Accidental Sampling. The total number of samples taken in this research is 60 people. The sampling process is conducted for 3 days conducted on Tuesdays, Wednesdays and Saturday by taking 20 sample per day. The results showed that product measured by number of varieties, quality and brand influence the buying decision. Place measured based on the location of the strategic place and the arrangement of interior decoration also affect the purchasy decision. The promotion measured based on the promotion given to the consumer influences the buying decision. While, the variable price measured by price, price of purchasing power, and price of quality product do not influence the repurchase decision.*lrr*.